Pengaruh Aplikasi Akupuntur Pada Pasien Hipertensi di Puskesmas Sentani Kabupaten Jayapura - Nompo, Rifki Sakinah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Hypertension is blood pressure that exceeds normal limits divided into three categories. Hypertension is dubbed as a silent killer with symptoms of feelings of bending, headaches, palpitations, blurred vision, ringing in the ears, fatigue, vertigo, and nosebleeds. In addition, trends in treatment using alternative and complementary therapies are starting to appeal to the community, one of which is acupuncture. Acupuncture is a method of treatment by attaching needles to certain points on the body to reduce blood pressure or relieve symptoms of hypertension. This study aims to determine the application of acupuncture at points: LV3, HT7, PC6, and LU9 in hypertensive patients. This research was an experimental pretest-posttest without a control group with a time series approach, in 15 people with blood pressure criteria â‰¥130mmHg. This research was conducted from November 2018 to February 2019 using the analysis of the repeated ANOVA test. The results of the comparative output mean it is known that average hypertension before the acupuncture application was 172.93 mmHg, and after the acupuncture application 155.87 mmHg at the first meeting, hypertension before the acupuncture application was 154.50 mmHg and after the acupuncture application was 135.73 mmHg at the second meeting with the results of the in-action effect test revealed a Greenhouse-Geisser sig value of 0,000, so it can be concluded that there is a difference in the decrease in average blood pressure in hypertensive patients. Efforts that can be done are monitoring the continuity of hypertensive patients in carrying out acupuncture therapy.